Public procurement for the formation of markets for innovation: Coordination failures and instruments - Chicot, Julien; Bleda, Mercedes (My University, 2016)
Public procurement essentially consists in the purchase of goods and/or services helping public administrations performing (better) their public services missions. Its role has evolved and it is increasingly used as an instrument to achieve additional socio-economic objectives such as fostering innovation. Public procurement of innovation has gained a renewed impetus in the academic literature too, which has been mostly focusing on its impacts on innovation and on impediments in the public procurement procedure.
Keywords: Contratos administrativos